2005
DOI: 10.1111/j.1365-2893.2005.00648.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between desialylated hepatitis B virus and asialoglycoprotein receptor on hepatocytes may be indispensable for viral binding and entry

Abstract: The cellular receptor for hepatitis B virus (HBV) infection has not yet been identified. The purpose of this study was to address the possibility of participation by desialylated HBV and the asialoglycoprotein receptor (ASGP-R) exclusively expressed on liver parenchymal cells, in infection. Assays for viral binding and entry were performed by culturing a hepatoblastoma cell line, HepG2, and HBV particles derived from the HBV carrier in the presence or absence of neuraminidase (NA). Viral binding and entry were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 50 publications
(84 reference statements)
0
16
0
Order By: Relevance
“…Although DHBV shares many molecular similarities with HBV, DHBV probably uses other receptors for primary attachment than GAGs (for a recent review, see Glebe and Urban, 2007). In a recent publication, Owada et al (2006) reported that treatment of HBV with sialidase during incubation with human hepatoma cell line HepG2 would result in infection via the ASGPR, a liver-specific lectin that is responsible for uptake of desialylated glycoproteins from blood into hepatocytes (Spiess, 1990) and has been proposed as a receptor for HBV (Treichel et al, 1994;1997). In previous studies, we could show that Nand O-glycans of HBV surface glycoproteins could be desialylated by treatment with sialidase (Schmitt et al, 1999;, resulting in increased binding to HepG2 cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although DHBV shares many molecular similarities with HBV, DHBV probably uses other receptors for primary attachment than GAGs (for a recent review, see Glebe and Urban, 2007). In a recent publication, Owada et al (2006) reported that treatment of HBV with sialidase during incubation with human hepatoma cell line HepG2 would result in infection via the ASGPR, a liver-specific lectin that is responsible for uptake of desialylated glycoproteins from blood into hepatocytes (Spiess, 1990) and has been proposed as a receptor for HBV (Treichel et al, 1994;1997). In previous studies, we could show that Nand O-glycans of HBV surface glycoproteins could be desialylated by treatment with sialidase (Schmitt et al, 1999;, resulting in increased binding to HepG2 cells .…”
Section: Discussionmentioning
confidence: 99%
“…The removal of the distinct sugars from cell-surface proteins was tested by shifting of the heavily N-glycosylated and sialylated asialoglycoprotein receptor (ASGPR) in SDS-PAGE immunoblots from plasmamembrane preparations of PTH (data not shown). Because the ASGPR is a liver-specific lectin, it had been speculated that it might serve as a specific receptor for HBV, especially during treatment of hepatocytes with sialidase (Owada et al, 2006). However, neither preincubation with sialidase, nor incubation in the presence of sialidase, resulted in significant increase or decrease of infection (Fig.…”
Section: Treatment Of Cells With Different Enzymes That Cleave Cell-smentioning
confidence: 99%
“…It is still unknown how long this antibody will persist in patients with chronic HBV and if Anti-asialoglycoprotein receptor-R [41] The asialoglycoprotein receptor is a liver specific glycoprotein of the cell membrane. Its main function is the internalization of asialoglycoproteins by binding a terminal galactose residue to coated pits [47]. Anti-asialoglycoprotein receptor-R may be a specific receptor for hepatitis B virus infection [48].…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…HBV infection results in 500,000 to 1.2 million deaths per year caused by chronic hepatitis, cirrhosis, and hepatocellular carcinoma and is the 10 th leading cause of death worldwide [3]. The mechanisms for persistent HBV infection are not fully understood, but they seem to involve several aspects, including genetic components [4]. The role of genetics components of the virus and the host in the natural history of hepatitis B including HBV genotypes and subgenotypes; basal core promoter and pre core mutations; HBV DNA serum levels and co-infection with other viruses (particularly hepatitis C and human immunodefficiency viruses) have been recently reviewed [5].…”
Section: Introductionmentioning
confidence: 99%